Analysis Of Factors Affecting Feet Sensitivity Disorders In Type 2 Diabetes Mellitus Patients - Indhit Tri Utami; Fitri Annisa (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Diabetes Mellitus is a disease that contributes to the highest number of deaths in the world with complications of microangiopathy which causes sensitivity disorders in the feet. The occurrence of foot sensitivity disorders in patients is the most frequent and serious condition in Type 2 Diabetes Mellitus. This study aims to determine the dominant factors among variables of age, gender, duration of diabetes mellitus, smoking history and hypertension. This research was conducted at the Tejo Agung Public Health Center in Lampung. The sample in this study amounted to 36 respondents with purposive sampling. Impaired foot sensitivity is done through the Ipswich Touch Test (IpTT) technique. Bivariate analysis using Spearman Rank Test and multivariate analysis using logistic regression test. The results showed that age was the dominant factor in the occurrence of foot sensitivity disorders with a p value of 0.002. Multivariate analysis through the regression equation obtained the value of 8.5%. DM patients type 2 are aged 50 years and suffer from hypertension, they have an 8 times risk of experiencing foot sensitivity disorders. This study is expected to provide education and monitoring for DM patients to carry out foot examinations so as to prevent complications such as diabetic ulcers